2017
DOI: 10.1104/pp.17.00374
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of Root Hair Development Genes in Vascular Plants

Abstract: ORCID IDs: 0000-0002-5135-6088 (L.H.); 0000-0002-0560-5872 (J.S.).The molecular genetic program for root hair development has been studied intensively in Arabidopsis (Arabidopsis thaliana). To understand the extent to which this program might operate in other plants, we conducted a large-scale comparative analysis of root hair development genes from diverse vascular plants, including eudicots, monocots, and a lycophyte. Combining phylogenetics and transcriptomics, we discovered conservation of a core set of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 63 publications
3
40
1
Order By: Relevance
“…However, nothing is known about the negative regulation of RSL class I genes in any other land plant. The role of GL2 as negative regulator of RSL class I genes and root hair development is not likely to be widely conserved because the closest homologs of GL2 in many other vascular plants are not expressed in roots ( Huang et al, 2017 ). Furthermore, GL2 genes have not been identified in bryophytes (liverworts, mosses and hornworts) ( Zalewski et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, nothing is known about the negative regulation of RSL class I genes in any other land plant. The role of GL2 as negative regulator of RSL class I genes and root hair development is not likely to be widely conserved because the closest homologs of GL2 in many other vascular plants are not expressed in roots ( Huang et al, 2017 ). Furthermore, GL2 genes have not been identified in bryophytes (liverworts, mosses and hornworts) ( Zalewski et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…FEBS Letters, 553(1-2): 113-118 ALA family and other P-type ATPases generated in Arabidopsis Heat Tree Viewer (http://arabidopsis-heattree.org), with ALA clusters (Baxter et al, 2003) bracketed by grey rectangles and thicker lines representing bootstrap values of 98 or greater. (B) Database expression profile of ALA4/5/6/7 genes in rosette, root, hypocotyl, trichomes, and mature pollen, generated from Arabidopsis eFP browser (Winter et al, 2007), with root hair data from Huang et al, 2017 Figure 5. Ectopic expression of ALA4 in pollen restores seed set and normal pollen transmission in an ala6/7 double KO.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…However, plant-specific Class III peroxidase can also generate ROS (Shigeto and Tsutsumi, 2016). Accordingly, several Class III peroxidase genes are highly induced during root hair development in higher plants (Huang et al, 2017;Moon et al, 2018). Results from our microarray and RT-qPCR analyses of the root hairs from Os07g39940-OX indicated that three genes encoding Class III peroxidase were up-regulated in the transgenics (Fig.…”
Section: Rsl Class II Subfamily Genes and Rhl1 Regulate Ros Levels Inmentioning
confidence: 82%